Systemic Glucose Administration Alters Water Diffusion and Microvascular Blood Flow in Mouse Hypothalamic Nuclei – An fMRI Study - Lizarbe, Blanca; Fernández-Pérez, Antonio; Caz, Victor; Largo, Carlota; Vallejo, Mario; López-Larrubia, Pilar; Cerdán, Sebastián (Frontiers in Neuroscience, 2019)
The hypothalamus is the principal regulator of global energy balance, enclosing additionally essential neuronal centers for glucose-sensing and osmoregulation. Disturbances in these tightly regulated neuronal networks are thought to underlie the development of severe pandemic syndromes, including obesity and diabetes. In this work, we investigate in vivo the response of individual hypothalamic nuclei to the i.p. administration of glucose or vehicle solutions, using two groups of adult male C57BL6/J fasted mice and a combination of non-invasive T2*-weighted and diffusion-weighted functional magnetic resonance imaging (fMRI) approaches. MRI parameters were assessed in both groups of animals before, during and in a post-stimulus phase, following the administration of glucose or vehicle solutions. Hypothalamic nuclei depicted different patterns of activation characterized by: (i) generalized glucose-induced increases of neuronal activation and perfusion-markers in the lateral hypothalamus, arcuate and dorsomedial nuclei, (ii) cellular shrinking events and decreases in microvascular blood flow in the dorsomedial, ventromedial and lateral hypothalamus, following the administration of vehicle solutions and (iii) increased neuronal activity markers and decreased microperfusion parameters in the ARC nuclei of vehicle-administered animals. Immunohistochemical studies performed after the post-stimulus phase confirmed the presence of c-Fos immunoreactive neurons in the arcuate nucleus from both animal groups, with significantly higher numbers in the glucose-treated animals. Together, our results reveal that fMRI methods are able to detect in vivo diverse patterns of glucose or vehicle-induced effects in the different hypothalamic nuclei.